PERILAKU DAN KEPUASAN KONSUMEN MAHASISWA UNIVERSITAS LAMPUNG TERHADAP MAKANAN CEPAT SAJI MENU UTAMA AYAM BAKAR [Customer Behavior and Satisfaction of the University of Lampung Students on Fast Food Grilled Chicken as the Main Menu] - Fibra Nurainy; Azhari Rangga; Mahesa Reyhan Prayoga (Jurnal Teknologi & Industri Hasil Pertanian, 2019)
This study aimed at knowing the behavior and consumer satisfaction of students at the University of Lampung on fast food products, and determining the level of importance and performance of attributes that influence the marketing mix recommendations. The study used a behavioral survey and customer satisfaction method, and was performed to survey 77 students. Data were analyzed using Importance-Performance Analysis, and Customer Satisfaction Index. The results showed that the initial motivation of consumers to buy was easy to obtain (29 people), and the benefit sought to eliminate hunger and had good taste (72 people). The main focus of the attributes was the taste (54 people) by which consumers who felt quite satisfied were 43 people and those who decided to buy back as many as 71 people. The results of the Importance-Performance Analysis showed that the main priority was the speed of preserving. Attributes that was suitable with the interests of consumers were spices, textures, product hygiene, friendliness in service and comfort of the place, while the low-performance attributes were product appearance, price discounts on specific activities, selection of advertising media used, preserving package and size per serving. The value analysis of the Customer Satisfaction Index (CSI) was 86.56%, that means the consumers feel very satisfied. Recommendations related to the marketing mix (7P) to be performed by producers were product variables improvement, namely appearance and preserving, and promotion products, such as price discounts on specific activities, as well as actively promoting on social media.